Synthesis of unsaturated phosphatidylinositol 4-phosphates and the effects of substrate unsaturation on SopB phosphatase activity. Issue 7 (17th December 2014) - Furse, Samuel; Mak, LokHang; Tate, Edward W.; Templer, Richard H.; Ces, Oscar; Woscholski, Rüdiger; Gaffney, Piers R. J.
Abstract : Single enantiomers of PI-4- P, with a range of sn -2-fatty acid esters, were prepared efficiently. The effects of the degree of sn -2-unsaturation on the kinetic parameters of Sop B were determined. Abstract : In this paper evidence is presented that the fatty acid component of an inositide substrate affects the kinetic parameters of the lipid phosphatase Salmonella Outer Protein B ( Sop B). A succinct route was used to prepare the naturally occurring enantiomer of phosphatidylinositol 4-phosphate (PI-4- P ) with saturated, as well as singly, triply and quadruply unsaturated, fatty acid esters, in four stages: (1) The enantiomers of 2, 3:5, 6- O -dicyclohexylidene- myo -inositol were resolved by crystallisation of their di(acetylmandelate) diastereoisomers. (2) The resulting diol was phosphorylated regio-selectively exclusively on the 1- O using the new reagent tri(2-cyanoethyl)phosphite. (3) With the 4-OH still unprotected, the glyceride was coupled using phosphate tri -ester methodology. (4) A final phosphorylation of the 4- O, followed by global deprotection under basic then acidic conditions, provided PI-4- P bearing a range of sn -1-stearoyl, sn -2-stearoyl, -oleoyl, -γ-linolenoyl and arachidonoyl, glycerides. Enzymological studies showed that the introduction of cis -unsaturated bonds has a measurable influence on the activity (relative V max ) of Sop B. Mono -unsaturated PI-4- P exhibited a five-fold higher activity, with a two-fold higher K M, over the saturated substrate, when presented in DOPC vesicles. Poly -unsaturated PI-4- P showed little further change with respect to the singly unsaturated species. This result, coupled with our previous report that saturated PI-4- P has much higher stored curvature elastic stress than PI, supports the hypothesis that the activity of inositide phosphatase Sop B has a physical role in vivo .